2016
DOI: 10.1080/15376516.2016.1217112
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette aerosol induces significantly less cytotoxicity than tobacco smoke

Abstract: Electronic cigarettes (E-cigarettes) are a potential means of addressing the harm to public health caused by tobacco smoking by offering smokers a less harmful means of receiving nicotine. As e-cigarettes are a relatively new phenomenon, there are limited scientific data on the longer-term health effects of their use. This study describes a robust in vitro method for assessing the cytotoxic response of e-cigarette aerosols that can be effectively compared with conventional cigarette smoke. This was measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 77 publications
6
96
1
2
Order By: Relevance
“…The toxicological assessment of e-cigarettes has so far reported fewer biological responses on cellular functions compared to conventional cigarettes 6,12,[25][26][27] , however, approaches for dose and matrices have been inconsistent. Yu and colleagues compared e-cigarette aerosol extracts with cigarette smoke extracts generated in media applied to both primary and immortalized epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxicological assessment of e-cigarettes has so far reported fewer biological responses on cellular functions compared to conventional cigarettes 6,12,[25][26][27] , however, approaches for dose and matrices have been inconsistent. Yu and colleagues compared e-cigarette aerosol extracts with cigarette smoke extracts generated in media applied to both primary and immortalized epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent e-cigarette studies, we have shown the importance of expressing dose as a function of delivered nicotine, when conducting comparative studies across different tobacco and nicotine product categories. Azzopardi et al 25 and Adamson et al 7,28 showed how deposited mass and nicotine quantification at the cellular exposure interface enable appropriate extrapolation and comparisons in an aerosol matrix. Different types of e-cigarettes and e-liquids generate different volumes of aerosol and deliver different amounts of nicotine, however typically smokers who switch from cigarette to nicotine delivery devices adapt their behavior to potentially titrate for nicotine 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…These differences could potentially explain the varying levels of the same chemical in the aerosol or a different degree of cardiac function impairment. To draw meaningful broad conclusions, there is, therefore, a need for better standardization of protocols (e.g., Azzopardi et al 2016;Farsalinos et al 2016c;Iskandar et al 2016). In addition, future researchers need to take advantage of other tools and methodologies such as randomized controlled trials (Cravo et al 2016), and develop mathematical models and new frameworks (Kalkhoran and Glantz 2015;Levy et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Complex in vitro tissue and organ models have been established that include assessment of cardiovascular and vascular systems. 9 …”
Section: Introductionmentioning
confidence: 99%